Neutrophil myeloperoxidase index in pediatric acute appendicitis - Stanković, Nikola D; Đorđević, Dragan; Rondović, Goran; Kostić, Zoran; Zeba, Snježana; Milosavljević, Snežana; Savić, Đorđe; Miličković, Maja; Grujić, Blagoje; Đuričić, Slaviša; Stanojevic, Ivan; Milanović, Marijana (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Diagnosis of acute appendicitis (AA) remains the most common dilemma of pediatric surgical team. Our aim was to determine whether the neutrophil myeloperoxidase index (MPXI), in combination with other laboratory and clinical parameters, can be useful in diagnosis and follow-up of AA in children. Methods. A prospective investigation of MPXI values in 117 consecutive patients, planned for the surgical intervention due to AA, was performed. The patients were stratified into three groups according to the intraoperative finding: the normal/early, uncomplicated and complicated AA. Laboratory analyses were done preoperativly, on the 1st and on the 3rd postoperative days. Results. The statistically significant difference of MPXI values between the uncomplicated and complicated appendicitis before surgery and the positive correlations between the MPXI and C-reactive protein, as well as interleukin-6, before surgery were found. Postoperatively, in the group of uncomplicated, as well as complicated AA, a significant decrease of MPXI was recorded. Conclusion. The MPXI may be used as an informative biomarker in the follow-up of AA in children. A wide reference range for the MPXI and individual differences in the values of MPXI in the healthy children, generate difficulties for its use for the initial diagnosis of acute appendicitis. Usefulness of MPXI determination decreases with a delayed diagnosis.